Clinical survey on contrast-induced nephropathy after coronary angiography. (14th August 2013) - Wang, Feng; Li, Junhui; Huang, Baorui; Zhao, Qing; Yu, Gang; Xuan, Changyou; Wei, Meng; Wang, Niansong
Abstract: Objective : To investigate the incidence and risk factors of contrast-induced nephropathy (CIN) in patients receiving coronary angiography (CAG) in a Chinese medical center. Methods : The medical records of the patients receiving CAG at Shanghai Sixth People's Hospital Affiliated to Shanghai Jiaotong University from January 2008 to July 2009 were collected to analyze the incidence of CIN under different conditions and the clinical difference between CIN group and non-CIN group. Results : There were 487 cases enrolled in this study and the total incidence of CIN was 10.5%. Through Mehran risk score stratification, incidence of CIN increased with risk scores and in an extremely high-risk group it was as high as 18.0%. Multi-factor regression analysis showed that preoperative hypotension, heart failure, anemia and low estimated glomerular filtration rate (≤30 mL/min) were risk factors of CIN after CAG. Conclusion : CIN post CAG is associated with preoperative hypotension, heart failure, anemia and renal function. Close attention should be paid to CIN in patients receiving CAG.